Pilares mistos de aço e concreto parcialmente revestidos: comportamento isolado, inserção em galpões industriais e comparativos com pilares de sistemas estruturais usuais - Serafim, Jorge Augusto (2013)
Despite the great use in most developed countries, the composite structures have been little exploited in Brazil, including rare records the use of composite columns of steel and concrete partially coated in industrial sheds. The low-use leaves the impression of this being a structural solution viable. The aim of this work is to insert the composite columns of steel and concrete partially coated alternatively to the pillars of steel and precast, solutions commonly used in the composition of the structural system of industrial sheds. The development work was done to study the behavior of the isolated element and sizing criteria applicable, analysis of the structural design of systems where it can be employed and the phases of project highlighting, still, some steps involved in constructive phase of the industrial sheds. We analyzed the elements of 108 sheds with variation in the span between 20 to 50 m and height of 8 to 12 m. the porticos were designed considering coverage using steel beams with profile type I and type I section steel pillars, pillars of precast concrete with rectangular section, composite columns of steel and concrete partially coated consisting of metallic profile type I with filling of concrete between the tables. The porticoes were analyzed in 2nd order and scaled according to the specific Brazilian standards by comparing the results obtained between structural systems. Costs despite the difficulties have been raised for the central region of the State of São Paulo, where, after the composition were made comparisons between the solutions. The results obtained can realize that the use of composite columns of steel and concrete partially coated are perfectly viable with visa point economic values quite surprising, for the fact of being a solution less maid. The use of composite columns of steel and concrete partially coated is obviously viable as an alternative to the usual structural systems used in industrial sheds, comes in to advance contribution of Civil construction in General.